Impact of High Volume Energy Drink Consumption on Electrocardiographic and Blood Pressure Parameters: A Randomized Trial. Issue 11 (4th June 2019) - Shah, Sachin A.; Szeto, Andy H.; Farewell, Raechel; Shek, Allen; Fan, Dorothy; Quach, Kathy N.; Bhattacharyya, Mouchumi; Elmiari, Jasmine; Chan, Winny; O'Dell, Kate; Nguyen, Nancy; McGaughey, Tracey J.; et al.
Abstract : Background: Energy drinks have been linked to an increase in emergency room visits and deaths. We aim to determine the impact of energy drinks on electrocardiographic and hemodynamic parameters in young healthy volunteers. Methods and Results: A randomized, double‐masked, placebo‐controlled, crossover study was conducted in healthy volunteers. Participants consumed 32 oz of either energy drink A, energy drink B, or placebo within 60 minutes on 3 study days with a 6‐day washout period in between. The primary end point of QTc interval and secondary end points of QT interval, PR interval, QRS duration, heart rate, and brachial and central blood pressures were measured at baseline, and every 30 minutes for 240 minutes. A repeated‐measures 2‐way analysis of variance was performed with the main effects of intervention, time, and an interaction of intervention and time. Thirty‐four participants were included (age 22.1±3.0 years). The interaction term of intervention and time was statistically significant for Bazett's corrected QT interval, Fridericia's corrected QT interval, QT, PR, QRS duration, heart rate, systolic blood pressure, diastolic blood pressure, central systolic blood pressure, and central diastolic blood pressure (all P <0.001). The maximum change from baseline in Bazett's corrected QT interval for drinks A, B, and placebo were +17.9±13.9, +19.6±15.8, and +11.9±11.1 ms, respectively ( P =0.005 for ANOVA) ( P =0.04 and <0.01, respectively compared with placebo). Peripheral and central systolic and diastolic blood pressure were statistically significantly different compared with placebo (all P <0.001). Conclusion: Energy drinks significantly prolong the QTc interval and raise blood pressure. Clinical Trial Registration: URL: http://www.clinicaltrials.gov . Unique identifier: NCT03196908. Abstract : See Editorial Winniford